Focus on customers? needs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A poultry farmer from South Africa explains how she has built up her business as a reliable supplier of poultry products, by focussing on the needs of her customers. This has included recruiting agents to sell her chickens, investing profits from the business in a vehicle to solve transport problems, developing a good system of communication with customers, and adding value to her chicken products.